Innovators and innovations in high quality wines of Argentina - Julio Elías; Gustavo Ferro (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2018)
How does the process of applying knowledge to the economy work? How do people innovate? What is inside the innovation black box? Can the process be stylized? We apply an economic approach to creativity which provides a general analytical framework to innovation to answer these questions by distinguishing two types of innovations: conceptual and experimental. The development of quality wines which in Argentina began in the 1990s was a process that involves both types of innovations. We analyze two cases of successful winemakers and we characterize their process of innovations to derive lessons with potential managerial and public policy implications.
Keywords: O31; Q13; 330; Innovation; Wine industry; Argentina